1999
DOI: 10.1046/j.1469-1809.1999.6350413.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns of mtDNA reflecting the colonization of the Canary Islands

Abstract: Although the Canary Islands were settled by humans, possibly of Berber origin, as late as 2500 years ago, the precise course and numbers of early migrations to the archipelago remain controversial. We have therefore analysed mtDNA variation (HVS‐I as well as selected RFLP sites) in 300 individuals from the seven Canary Islands. The distribution and variation across the islands in a specific mtDNA clade of Northwest African ancestry suggest that there was one dominant initial settlement process that affected al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
152
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(172 citation statements)
references
References 24 publications
16
152
4
Order By: Relevance
“…An exceptional case was El Hierro, for which the genetic distances, although non-significant, point to a closer affinity with Northwest Africans than Iberians. This distinctiveness could be due to a higher sub-Saharan African influence in this Island, as has been observed for mtDNA (Rando et al 1999, Flores et al 2001a) and the Y chromosome (Flores et al 2003). However, it should be noted that the distance between Canarians and Northwest Africans were two times smaller than those between Iberians and Northwest Africans (Table 2).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…An exceptional case was El Hierro, for which the genetic distances, although non-significant, point to a closer affinity with Northwest Africans than Iberians. This distinctiveness could be due to a higher sub-Saharan African influence in this Island, as has been observed for mtDNA (Rando et al 1999, Flores et al 2001a) and the Y chromosome (Flores et al 2003). However, it should be noted that the distance between Canarians and Northwest Africans were two times smaller than those between Iberians and Northwest Africans (Table 2).…”
Section: Resultssupporting
confidence: 56%
“…Particularly, in the case of the Canary Islands, both have provided a more reliable vision of the genetic composition of the present day population. From mtDNA data, besides the sub-Saharan African influence, a more important Northwest African one was detected (Pinto et al 1996;Rando et al 1999). Furthermore, ancient mtDNA has demonstrated that this Northwest African influence is not only due to slavery but mostly due to aborigine heritage (Maca-Meyer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies on diversity and frequency distribution of polymorphic markers in the current populations of the seven islands have also given inconclusive results. The correlation patterns found for mtDNA, CD4/Alu haplotypes, and AB0 allele frequencies were congruent with only one dominant settlement process, 2,3,10 whereas the distribution and dating of some Y-chromosome North African lineages, present in the Canary Islands, matched with a pattern of settlement of the archipelago in two stages. 4 If the aboriginal colonizers reached the islands by themselves, using primitive boating skills, they most probably landed first on the nearest eastern islands from the mainland and, under demographic pressure, ventured afterwards to the next western island at sight.…”
Section: Introductionmentioning
confidence: 65%
“…This apparent discrepancy was due to the fact that exact L haplotypic matches between North Africa and the historical sample from Tenerife 5 were greater than between the former and Gran Canaria. 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation